Inoculum and disease dynamics of citrus greasy spot caused by Zasmidium citri-griseum in sweet orange in Panama - Aguilera-Cogley, Vidal; Sedano, Maria E.; Vicent, Antonio (Wiley Online Library, 2023)
Citrus greasy spot, caused by Zasmidium citri-griseum, is a disease characterized by inducing premature defoliation and a reduction in yield in different citrus species. Greasy spot is the most prevalent fungal disease in sweet orange in Panama. Nevertheless, no epidemiological information is available. In this study, the dynamics of the defoliation, inoculum production, airborne inoculum and infection periods of Z. citri-griseum and their associations with environmental conditions were determined in Panama. The period from December to April was characterized by greater defoliation of trees, with the greatest amount of leaf litter being produced in January and February. The number of days until total leaf decomposition (DLD) was related to the number of rainy days >1 mm (NRD), accumulated rainfall (AR) and average relative humidity (ARH). The number of ascospores released from leaf litter (ASCL) was related to DLD, NRD, AR and average temperature (AT). The greatest amounts of airborne ascospores (AASC) of Z. citri-griseum occurred during April and May, when the rainy season begins in Panama. Similarly, the highest incidence (INC) of greasy spot in the trap plants coincided with the months of the greatest availability of airborne ascospores. However, infections were also recorded during other times of the year. The AASC or INC data were fitted to Bayesian models including meteorological variables and an autoregressive temporal component, the latter being the most influential. The results obtained in this study will allow the development of more efficient and sustainable fungicide programmes for greasy spot control in Panama.